2019
DOI: 10.1177/0300060519864808
|View full text |Cite
|
Sign up to set email alerts
|

Atypical hemolytic uremic syndrome in a patient with protein-losing enteropathy

Abstract: Atypical hemolytic uremic syndrome (aHUS) is an ultra-rare disease induced by many triggers, all of which produce a common end phenotype of microangiopathic hemolysis and thrombotic microangiopathy. We herein describe a 63-year-old woman with ongoing protein-losing enteropathy and frequent transudates caused by hypoalbuminemia. The patient was treated with eculizumab with a full hematologic and partial renal response. Protein-losing enteropathy is an inflammatory condition that has been linked with increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Similar CFH gene mutations have been shown in the literature to accelerate the predisposition to aHUS and the development of lupus nephritis in accurate mouse models (MRL-lpr mice) [8]. Diagnosis of aHUS is done after exclusion of other microangiopathic hemolytic anemias and with possible findings of a pathologic variant mutation or deletion [3]. Traditional therapies include plasma exchange, glucocorticoids, and immune therapies, but recent clinical trials have shown complement inhibition with eculizumab to induce remission of acute episodes of aHUS and prevention of TMA events refractory to plasma therapy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar CFH gene mutations have been shown in the literature to accelerate the predisposition to aHUS and the development of lupus nephritis in accurate mouse models (MRL-lpr mice) [8]. Diagnosis of aHUS is done after exclusion of other microangiopathic hemolytic anemias and with possible findings of a pathologic variant mutation or deletion [3]. Traditional therapies include plasma exchange, glucocorticoids, and immune therapies, but recent clinical trials have shown complement inhibition with eculizumab to induce remission of acute episodes of aHUS and prevention of TMA events refractory to plasma therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The activation of the alternative pathway of the complement system in hemolytic uremic syndrome has been known since 1975 [1][2][3]. The complement system plays an important part in the adaptive and innate immune systems and consists of more than 40 plasma and membrane-associated proteins [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thrombomodulin mutation identified is a recognized pathogenic variant of alternative complement pathway dysfunction. 11 , 12 The lack of peripheral hemolysis suggests a renal limited TMA presentation, despite the finding of low platelets systemically. It is important to note that the lack of systemic hemolysis does not preclude the existence of TMA, and the finding seen in this case is reminiscent of Timmermans et al 13 about arteriolar injury and complement dysfunction in patients with chronic hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are many complex pathways involved; however, it has become clear that endothelial injury can occur more easily in certain genetically susceptible individuals. 2 It has also been observed that if endothelial damage and complement activation are sufficiently severe, TMA can occur despite the appearance of an apparently benign genetic environment. 3 Scleroderma renal crisis (SRC) usually presents with a TMA that occurs within the context of malignant hypertension (MHT) and progressive renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%